Efeito do condicionamento com diferentes concentrações de ácido fluorídrico sobre a resistência de união entre cerâmica e bráquetes metálicos - Arend, Cristiane Frantz (2014)
Prior conditioning of the feldspathic ceramic surface is necessary to provide sufficient adhesion of brackets in this surface. The aim of this study was to evaluate the effect of etching with different hydrofluoric acid (HF) concentrations on the shear bond strength between glazed feldspathic ceramic and metal brackets. Seventy-five blocks of glazed feldspathic ceramic (VM9, Vita Zahnfabrik, Germany) were produced and randomized to 5 experimental groups: Ctrl- silane application only; HF1- HF 1% + silane; HF3- HF 3% + silane; HF5- HF 5% + silane; HF10- HF 10% + silane. HF and silane were applied for 1 and 5 minutes, respectively. Metal brackets of upper central incisor (Edgewise Standard 022"X030" slot, Dental Morelli, Brazil) were bonded on the ceramic surface, using an adhesive system and composite resin (TransbondTM XT, 3M Unitek, Brazil) and light-cured. Specimens were aged for 60 days (thermocycling 10000 cycles 5-55 °C; storage in distilled water at 37 °C). Shear testing was performed in a universal testing machine and specimens were classified for their Adhesive Remnant Index (ARI). Topographical inspection and contact angle analysis of the etched ceramic surfaces were performed. Data were statistically analyzed (p < 0,05). Kruskal-Wallis test did not detect significant differences among groups for bond strength values. ANOVA 1-factor showed that the etching had a significant influence on the contact angle results (p < 0.00001), since the control group presented the highest mean (61.8 ± 17.2°) when compared with the other groups (Tukey test). All specimens showed adhesive failures at the resin-ceramic interface. Based on the results, we can conclude that the use of HF did not influence significantly the shear bond strength of metal brackets bonded to the glazed feldsphatic ceramic surface, even though its use promoted the increase of the contact angle and changed of the topography surface.